2005
DOI: 10.1128/aac.49.8.3297-3301.2005
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence of In Vitro and In Vivo Fluconazole Dose-Response Curves for Cryptococcus neoformans

Abstract: We conducted in vitro experiments to evaluate the susceptibility of a clinical isolate of Cryptococcus neoformans to a wide range of concentrations of fluconazole. In vitro susceptibility was tested using broth macrodilution methods modified to provide a numeric count of viable organisms. The association between the quantitative in vitro response and fluconazole drug concentrations was estimated using local nonparametric regression. Regression analysis was used to assess the correspondence between the in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Experimental studies in mice and retrospective clinical studies suggest that the MIC (or other in vitro measures of antifungal potency-see, for example, Bauer et al [24]) is an important prognostic factor for determining the ultimate clinical outcome (22,(25)(26)(27)(28). For example, the probability of clinical failure in pa- mg/kg/day of fluconazole orally.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in mice and retrospective clinical studies suggest that the MIC (or other in vitro measures of antifungal potency-see, for example, Bauer et al [24]) is an important prognostic factor for determining the ultimate clinical outcome (22,(25)(26)(27)(28). For example, the probability of clinical failure in pa- mg/kg/day of fluconazole orally.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no relationship between in vitro data and early outcome was found for any of the three drugs. For fluconazole, a recent experimental study showed a correspondence of in vitro and in vivo dose-response curves for one isolate of C. neoformans (13). Nevertheless, it has also been shown in an experimental model of disseminated cryptococcosis that factors other than the MIC, such as the size of the fungal burden in the brain, influenced the in vivo efficacy of fluconazole (14).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, in the current study, Canadian isolates had significantly lower MICs to FLC than isolates from Australia. Most studies evaluating the correlation between in vitro susceptibility and the in vivo response to antifungal drugs have demonstrated that susceptibility testing is a reliable predictor of clinical response (22,47) and that the clinical outcome may be poorer when higher concentrations of FLC are required (MIC Ն 16 mg/liter) (1).…”
Section: Vol 48 2010 Antifungal Susceptibility In Cryptococcus Genomentioning
confidence: 99%